What is the philosophy of technology? - Pitt, Joseph C. (Mechane, 2020)
I argue that there is no such thing as Technology simpliciter but there are technological infrastructures which make it possible for us to do what we do. Likewise, there is no such thing as the philosophy of technology. Philosophizing is an activity – it is doing something. We do philosophy of technology. In particular, doing philosophy of technology is to consider how new instrumentalities change our understanding of what can be known and what we should be doing in the light of that new knowledge.